2008
DOI: 10.1093/ije/dyn226
|View full text |Cite
|
Sign up to set email alerts
|

Challenging assumptions about women's empowerment: social and economic resources and domestic violence among young married women in urban South India

Abstract: Efforts to help women empower themselves through vocational training, employment opportunities and social groups need to consider the potential unintended consequences for these women, such as an increased risk of domestic violence. The study findings suggest that the effectiveness of anti-dowry laws may be limited without additional strategies that mobilize women, families and communities to challenge the widespread acceptance of dowry and to promote gender equity. Longitudinal studies are needed to elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
178
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 21 publications
19
178
3
Order By: Relevance
“…[4] Few studies [5,6] have shown the prevalence of domestic violence to be higher in slum population than in general population. Studies done in slum population in Bangalore [5] and Kolkotta [6] have reported it as 50% and 66%, respectively, whereas relevant data are scarce in Bhubaneswar, the capital city of Odisha, a state in Eastern India. …”
Section: Introductionmentioning
confidence: 99%
“…[4] Few studies [5,6] have shown the prevalence of domestic violence to be higher in slum population than in general population. Studies done in slum population in Bangalore [5] and Kolkotta [6] have reported it as 50% and 66%, respectively, whereas relevant data are scarce in Bhubaneswar, the capital city of Odisha, a state in Eastern India. …”
Section: Introductionmentioning
confidence: 99%
“…8,16 According to NFHS3 survey 35% of women aged 15-49 in India have experienced physical or sexual violence. 3 According to study done by Ali lifetime prevalence of physical violence was 57.6% in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Employed women have been found to report violence more frequently than unemployed women in a number of other studies. [11][12][13] There are still grey areas in the understanding of IPV, its various forms and different factors bearing influence on it.…”
Section: Introductionmentioning
confidence: 99%
“…21 Deininger, Goyal, and Nagarajan 2013. 22 Rocca et al 2008. norms, and the reforms led to positive effects in regions where prevailing norms were favorable toward women and negative effects in regions where the prevailing norms were more patriarchal. In addition to the effect of societal norms, it is also possible for cultural elites to mediate pro-gender institutional reforms either through the socialization channel or the institutional channel.…”
Section: Property Rights Culture and Gender Outcomesmentioning
confidence: 99%